Oral health practices during first 1000 days of life: Literature review: Practicas de salud bucal durante los primeros 1000 días de vida: Revisión de la literatura - Sihuay-Torres, Kamila (2023)
Objective: To review the updated narrative literature on good oral health practices during the first 1000 days of life, that is, from gestation to two years of age. Materials and methods: A literature search was carried out in Pubmed and Scopus databases on february and march 2022. Original articles, and systematic reviews with or without meta-analysis, from 2016 to 2022 were included. For this purpose, search strategies were used with keywords in English taken from MeSH, such as: "prenatal care" AND ("dentistry" OR "oral health") / ("Pregnancy" OR "Infant") AND ("Oral Hygiene" OR "Toothbrushing" OR "Toothpaste") / (“Pregnancy” OR “Infant”) AND (“Prenatal nutrition” OR “Child Nutrition” OR "Breast feeding") / (“Pregnancy” OR “Infant”) AND “sugar intake” / “Infant” AND ("sucking behavior" OR "Nail biting") AND "dental occlusion" / (“Pregnancy” OR “Infant”) AND ("dental care" OR “Pediatric dentistry”). Results: Using the search criteria, 72 articles were selected to describe good oral health practices during the first 1000 days. This was divided into good oral hygiene practices, good dietary practices, parafunctional habits, and visits to the dentist. Conclusion: For good oral health during the first 1000 days of life, brush your baby's teeth with fluoride toothpaste from the first tooth eruption, avoid the consumption of free sugars, encourage breastfeeding instead of bottle-feeding, and visit the dentist since the pregnancy.